Spatial mismatches between plant biodiversity facets and evolutionary legacy in the vicinity of a major Mediterranean city. (January 2016) - Pouget, M.; Youssef, S.; Dumas, P.-J.; Baumberger, T.; San Roman, A.; Torre, F.; Affre, L.; Médail, F.; Baumel, A.
Highlights: Plant biodiversity facets are spatially mismatched and unequally protected. Species biodiversity facets are not effective surrogate of evolutionary legacy. Phylogeography was used to evaluate different conservation targets near a big city. Abstract: The analyses of congruencies among biodiversity components address the issue of conservation priorities, but previously they have been done at coarse scales with limited relevance for conservation actions. Moreover, these former studies consider only the species level components of biodiversity and not the intra-specific evolutionary legacy that influences future biodiversity. This study represents the first assessment of congruencies between various components of plant biodiversity and the evolutionary legacy of a narrow endemic taxon ( Arenaria provincialis, Caryophyllaceae). Assessment is conducted in the vicinity of a Mediterranean big city (Marseille, S.E. France) where habitats and flora are threatened by mass tourism and urban sprawl. Our analyses reveal that the different plant biodiversity facets assessed are spatially mismatched and unequally protected. Moreover, by using only species-level components of biodiversity as conservation targets we ignore crucial areas for the evolutionary legacy of this narrow endemic plant. Our results highlight the crucial role of phylogeography as a criterion to target the genetic precursors of future biodiversity in conservation planning.